Blue and Long-Wave Ultraviolet Light Induce in vitro Neutrophil Extracellular Trap (NET) Formation - Neubert, Elsa; Bach, Katharina Marie; Busse, Julia; Bogeski, Ivan; Schön, Michael P.; Kruss, Sebastian; Erpenbeck, Luise (Frontiers in Immunology, 2019)
Neutrophil Extracellular Traps (NETs) are produced by neutrophilic granulocytes and consist of decondensed chromatin decorated with antimicrobial peptides. They defend the organism against intruders and are released upon various stimuli including pathogens, mediators of inflammation or chemical triggers. NET formation is also involved in inflammatory, cardiovascular, malignant diseases and autoimmune disorders like rheumatoid arthritis, psoriasis or systemic lupus erythematosus (SLE). In many autoimmune diseases like SLE or dermatomyositis, light of the ultraviolet-visible (UV-VIS) spectrum is well known to trigger and aggravate disease severity. However, the underlying connection between NET formation, light exposure and disease exacerbation remains elusive. We studied the effect of UVA (375 nm), blue (470 nm) and green (565 nm) light on NETosis in human neutrophils ex vivo. Our results show a dose- and wavelength-dependent induction of NETosis. Light-induced NETosis depended on the generation of extracellular reactive oxygen species (ROS) induced by riboflavin excitation and its subsequent reaction with tryptophan. The light-induced NETosis required both neutrophil elastase (NE) as well as myeloperoxidase (MPO) activation and induced histone citrullination. These findings suggest that NET formation as a response to light could be the hitherto missing link between elevated susceptibility to NET formation in autoimmune patients and photosensitivity for example in SLE and dermatomyositis patients. This novel connection could provide a clue for a deeper understanding of light-sensitive diseases in general and for the development of new pharmacological strategies to avoid disease exacerbation upon light exposure.